Research on the breakeven point in milk and meat production at ruminants - Rodica Chetroiu; Vili Dragomir (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Profitability in animal production is at the forefront of approaches and activities continuity, and the breakeven point, or equilibrium point from which profit generation begins, must be reached in the shortest possible time. In the present paper, the breakeven point is analyzed for cow's, sheep's, goat's and buffalo's milk, as well as for beef and sheep meat. The study is based on a total of 197 case studies conducted in ruminant farms of the aforementioned species, with average data for 3 consecutive years: 2017-2019, or 2018-2020. It turned out that the breakeven point synthesizes in its structure the levels of important technical-economic indicators of the activity, such as: the level of production and its capitalization price, which give the value of production, as well as variable and fixed costs. Thus, for the threshold of profitability in physical expression, the following average values were highlighted: for cow's milk 5,506.3 l / head, for beef 378.1 kg / head, for buffalo milk 801 l / head, for sheep milk 153.4 l / head, for sheep meat 17.9 kg / head, for goat's milk 216.1 l / head.
Keywords: Q01; Q12; Q13; 330; breakeven point; production; milk; meat; costs